The Effectiveness of Education with Animated Videos on Knowledge of Musculoskeletal Disorders and Postural Habits in Adolescents - Yuni Ardani, Madia; Nani, Desiyani; Hidayat, Arif Imam; Fa-is Walohtae (Window of Health : Jurnal Kesehatan, 2024)
Musculoskeletal disorders (MSDs) are disorders that occur in muscles, nerves, tendons, ligaments, bones, and joints. Complaints of MSDs often occur in adolescent school-age individuals, thus requiring health education through animated video media regarding early prevention of musculoskeletal disorders and ergonomic attitudes. This study aims to identify the influence of using animated videos on the level of knowledge of musculoskeletal disorders (MSDs) and postural habits and to analyze the relationship between MSDs knowledge and postural habits. This research used a Quasi-Experimental method with a pretest-posttest approach with a control group. The convenience sampling technique was used with 75 samples. Data analysis used univariate and bivariate analysis, namely with difference and cross-tabulation tests. The results of the study showed that the majority of respondents were female, 16 years old, with normal body mass index (BMI), parents' education level of high school, and income above the minimum wage. There were differences in the level of knowledge of musculoskeletal disorders (MSDs) and postural habits in the intervention and control groups, with obtained values of p = 0.006 and p = 0.016 (p < α, α = 0.05). There was a relationship between the level of knowledge of musculoskeletal disorders (MSDs) and postural habits, with an obtained value of p = 0.013 (p < α, α = 0.05). Thus, it is concluded that the provision of animated videos significantly influences knowledge of musculoskeletal disorders (MSDs) and postural habits.